2003
DOI: 10.5182/jaie.14.supplement_21
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Mono-, Di-, Tri- and Tetra-Glycine by Mesoporous Materials FSM-16

Abstract: Adsorption of mono, di-, tri-and tetra-gly by FSM-16 was attempted and isotherms for adsorption of them was drawn.The isotherms for adsorption were arranged from high to low that of tetra-, tri-, di-and mono-gly in order.The arrangement of the isotherms was dependent on the solubility of glycine and its oligomers. On the other hand, FSM-16 can function as the molecular sieve because FSM-16 has a mesopore.The effect of the molecular sieve showed very little in extend of the adsorption. IntroductionA mesoporous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…[6,7] The mesopores may also be used as reaction vessels in which new nanomaterials can be synthesized. [6,7] The mesopores may also be used as reaction vessels in which new nanomaterials can be synthesized.…”
Section: Reprintsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7] The mesopores may also be used as reaction vessels in which new nanomaterials can be synthesized. [6,7] The mesopores may also be used as reaction vessels in which new nanomaterials can be synthesized.…”
Section: Reprintsmentioning
confidence: 99%
“…[10,11] There is not much information in the literature on the removal of organic compounds and metal ions by mesoporous materials. [6] For organic pollutants, Zama et al found that FSM-16 grafted by Mo complexes could photocatalyze the hydroxylation of benzene to phenol using hydrogen peroxide as an oxidant under the irradiation of UV-light. FSM-16 showed a large capacity for adsorbing the enzyme when the pore sizes were larger than 5 nm.…”
Section: Reprintsmentioning
confidence: 99%